IMPLEMENTATION OF THE DECISION ON COMPETENCY STANDARDS FOR HIGH-LEADER PRATAMADI POSITIONS IN THE GOVERNMENT OF EAST BOLAANG MONGONDOW REGENCY - Aditya, Gusti; Mokat, JEH; Siwi, Devie SR (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2025)
This study aims to analyze the implementation of the Minister of Administrative and Bureaucratic Reform Decree No. 409 of 2019 concerning the Competency Standards for Primary High-Level Leadership Positions (JPTP) in East Bolaang Mongondow Regency. The research focuses on the implementation of the policy in the position filling process and its supporting and inhibiting factors. The results indicate that implementation is not optimal due to continuing discrepancies in educational qualifications, limited training, and political influence. However, there is an increasing commitment to the merit system and transparency of selection. This study’s recommendations emphasize the importance of strengthening the capacity of the BKPSDM, ongoing training, and digitizing the ASN information system.